Some Results Involving the Splitting Operation on Binary Matroids. (16th December 2012) - Pirouz, Naiyer; Shikare, Maruti Mukinda
Abstract : We obtain some results concerning the planarity and graphicness of the splitting matroids. Further, we explore the effect of splitting operation on the sum of two matroids.